1141 NUMARALI VE 1593-1595 TARİHLİ TAHVÎL DEFTERİ (TRANSKRİPSİYON-DEĞERLENDİRME-DİZİN) - YILDIRIM, FİLİZ (Fırat Üniveristesi, 2010)
Bu çalışmamızda 1593-1595 yıllarında Osmanlı Devleti'nde merkezi hükümet tarafından yapılan atama kayıtları incelenmiştir. Merkez teşkilatından ziyade, Osmanlı taşrası hakkında önemli bilgiler elde ettiğimiz bu defterde, devletin bu zamandaki idari yapısı, eyalet, sancak ve kazalarıyla tespit edilmiştir. Atamaların nasıl yapıldığı, atama süreleri, yöneticilerin kaç akçeyle atandıkları hakkında da bir değerlendirme yapılmıştır.Anahtar Kelimeler: Eyalet, Sancak, Kaza, Tevcih, Atama.

In our study, assignment registers which were made by the Central Goverment of the Ottaman Empires within the years between 1593-1595 are examined. This regiser which we have gotten significant information on the Ottaman provinces rather than Central Goverment offers administrational structure of the State including districts and subdivision of the districits. A detailed assessment was also made to understand how to assign, assigntmental period, how much money is needed to appoint a director to do those jobs.Key Words: State, Sanjak, Administrative, Aiming, Assignment.
Bond Register Marked with 1141 and period of 1593-1595 (transcription-assessment-directory)
Keywords: Tarih